The Ideological Representation of Appraisal Resources in Nadiem Makarim’s Speech at the G20 - Shabriani, Elfrida (English Education Journal, 2023)
The capacity for representatives of a nation in international events to express their personal feelings and viewpoints is crucial for delivering effective speeches and shaping political beliefs and perspectives on global issues. Within the Systemic Functional Linguistics framework, the study applies the appraisal theory (Martin & White, 2005) to understand how the speaker manipulates language to convey his intended meaning. The primary objectives of this study are to identify the appraisal resources used in the speech and to uncover the ideological portrayal of these resources. In this study, the qualitative method was employed, with the unit of analysis focused on the appraising items found in Nadiem Makarim's speech text at the G20 Summit. Following the analysis and interpretation of the data, it is presented in a detailed explanation based on the three dimensions of critical discourse. The findings revealed that the most prominent domain utilized in the speech was attitude, enabling the speaker to express personal judgments, emotions, and evaluations regarding the propositions presented. Moreover, Makarim frequently employed positive assessment to praise the government's efforts and positively portray his reforms, presenting the government as a competent and reformative entity to gain support for his policy initiatives. This study is noteworthy as it offers a different perspective on discourse by integrating appraisal analysis and Critical Discourse Analysis (CDA) to reveal the underlying ideology.